Getting to transplantation. Issue 1 (15th September 2017) - Mulvihill, Michael S.; Hartwig, Matthew G.
Abstract : Continuous enhancements in mechanical support systems are redefining management of pretransplant candidates and require further refinement in the assessment and care of patients with end‐stage lung disease. See Hayanga et al's article onpage 125 .